2014
DOI: 10.1177/1541344614548589
|View full text |Cite
|
Sign up to set email alerts
|

Researching the Practice of Fostering Transformative Learning

Abstract: This article identifies factors that have contributed to the challenges associated with the practice and research of fostering transformative learning (TL), by drawing on the work by Rachal and others in reviewing the study of andragogy—theory, research, and practice. Implications are also discussed of how scholars of TL can best respond to the challenges identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(150 citation statements)
references
References 25 publications
2
94
0
1
Order By: Relevance
“…The different learning processes such as transformative learning [66][67][68], (emphasizes on change in thoughts, perceptions, and actions through critical reflection), social learning (focuses on the learning through social interaction and participation), and critical learning [69] (learning process that opens up a new lens of perception based on critical reflection developed through social contextual experiences) are essential for developing competence to understand the context and co-operate with a variety of partners involved in the innovation process. Mezirow [67] recognized that transformative learning involves an important aspect of learning in adulthood which provides adults with a new point of view to see the world as a result of the perception of their own past experiences [67]; the adult learning is largely understood as a means of improvement of the well-being of society [70].…”
Section: Embedding Social Innovation In Education (Learning Theories)mentioning
confidence: 99%
“…The different learning processes such as transformative learning [66][67][68], (emphasizes on change in thoughts, perceptions, and actions through critical reflection), social learning (focuses on the learning through social interaction and participation), and critical learning [69] (learning process that opens up a new lens of perception based on critical reflection developed through social contextual experiences) are essential for developing competence to understand the context and co-operate with a variety of partners involved in the innovation process. Mezirow [67] recognized that transformative learning involves an important aspect of learning in adulthood which provides adults with a new point of view to see the world as a result of the perception of their own past experiences [67]; the adult learning is largely understood as a means of improvement of the well-being of society [70].…”
Section: Embedding Social Innovation In Education (Learning Theories)mentioning
confidence: 99%
“…In addition to confirming Mezirow's ideal conditions for encouraging transformative learning, Taylor (2009) uncovered six interdependent elements that nurture transformative learning in educational settings. First, individual experience, including a learners' prior experiences as well as what he/she is experiencing in the learning situation is necessary to stimulate transformative learning (Taylor, 2009;Taylor & Laros, 2014). Taylor found that nurses with more experience may be able to take in new points of view more easily that those with less experience (Craigg, Plotnikoff, Hugo, & Casey, 2001 as cited in Taylor, 2009).…”
Section: Elements That Foster Transformative Learningmentioning
confidence: 99%
“…Hal ini memang mengesankan aspek kognitif yang kentara dalam transformasi yang dimaksudkan oleh Mezirow, dan menjadi salah satu celah kritik dari berbagai pihak. Beberapa peneliti kemudian menekankan pula pentingnya menambahkan dimensi emosional dan sosial sebagai target transformasi (Cranton, 2005;Dirkx, 1998Dirkx, , 2006Taylor, 2009). Bahkan lebih jauh, transformasi personal multidimensional tersebut dianggap perlu untuk diposisikan dalam bingkai kekuatan politik, ekonomi, dan sosial yang lebih luas.…”
Section: Gambar 1 Model Fase Pembelajaran Transformatif Nerstromunclassified